3D variability analysis reveals a hidden conformational change controlling ammonia transport in human asparagine synthetase - Adriana Coricello; Alanya J. Nardone; Antonio Lupia; Carmen Gratteri; Matthijn Vos; Vincent Chaptal; Stefano Alcaro; Wen Zhu; Yuichiro Takagi; Nigel G. J. Richards (Nature Communications)
Abstract Advances in X-ray crystallography and cryogenic electron microscopy (cryo-EM) offer the promise of elucidating functionally relevant conformational changes that are not easily studied by other biophysical methods. Here we show that 3D variability analysis (3DVA) of the cryo-EM map for wild-type (WT) human asparagine synthetase (ASNS) identifies a functional role for the Arg-142 side chain and test this hypothesis experimentally by characterizing the R142I variant in which Arg-142 is replaced by isoleucine. Support for Arg-142 playing a role in the intramolecular translocation of ammonia between the active site of the enzyme is provided by the glutamine-dependent synthetase activity of the R142 variant relative to WT ASNS, and MD simulations provide a possible molecular mechanism for these findings. Combining 3DVA with MD simulations is a generally applicable approach to generate testable hypotheses of how conformational changes in buried side chains might regulate function in enzymes.